Low cost carriers in the Middle East and North Africa: Prospects and strategies - Morrison, William G.; Mason, Keith J. (Elsevier, 2016)
We examine socio-economic indicators relevant to ‘low cost carriers’ (LCCs) in the Middle East and North Africa (MENA) and review the evolution of air transport liberalization and air service agreements in the region. We analyse the business strategies of MENA-based LCCs and using a benchmarking methodology, we compare the business strategy of Air Arabia Group with those of dominant European LCCs EasyJet and Ryanair. Our economic development indicators suggest future potential for LCC growth in Iran and Saudi Arabia while other MENA countries continue to face challenges. The lack of success in regional liberalization in air transport is restricting LCC growth although individual MENA countries have or will beneﬁt from ‘open skies’ agreements. MENA-based LCCs while retaining some characteristics of the LCC model also deviate in signiﬁcant ways. Benchmarking analysis shows that Air Arabia's business strategy represents a departure from the business strategies that have been most successful in Europe.
Keywords: Low cost carriers; MENA